Academic Identity, School Belongingness, Athletic Identity, and Athletic Expectations as Predictors of Academic and Athletic Time Use of College Athletes - Santos Jay C.; Sagas Michael (Sciendo, 2023)
Time demands are among the primary challenges for college student-athletes. They have to attend to classes and study halls as well as athletic-related activities such as training and competition. Both academic and athletic tasks require tremendous amount of time. Thus, it is argued that academics and athletics compete for the student-athletes' attention. This research examined the impact of academic and athletic factors on student-athletes' time use in academics and athletics using a subset of the 2015 United States National Collegiate Athletic Association (NCAA) GOALS data. The relationships of academic identity, school belongingness, athletic identity, and athletic expectations with academic time use and athletic time spent were tested. Differences on the variables of interest according to race, gender, and division level were also investigated. Our findings revealed that academic identity is a positive predictor of academic time use and a negative predictor of athletic time use, while athletic identity is a positive predictor of athletic time spent. We also determined a contrasting influence of athletic expectations in time commitments. Lastly, we likewise found significant effects of race, gender, and division level on the academic and athletic engagements of college athletes. Our findings have implications on the development of programs for athletic department to optimize the academic and athletic experiences of college student-athletes.